Critical Reflection of Female Reality in Physical Education at High Schools in the Municipality of Surakarta - Gunadi, Dwi; Rahayu, Tandiyo; Soegiyanto, Soegiyanto; Sulaiman, Sulaiman (The Journal of Educational Development, 2017)
In a social order until recently, the male and female status is still often being debated. This discourse is increasingly phenomenal in sports and physical education which often firmly create problems of dichotomy between men and women both in the perspective of sex and gender. This study aims to explore the extent to which the understanding of the concept of gender ideology is among teachers,  high school students, stakeholders, and the public in the municipality of Surakarta and their implications in physical education. This research is designed as a qualitative descriptive exploratory study. The social setting as the object of this research is High School (SMA) in the municipality of Surakarta. The techniques of data collection employed in this research were deep interviews, observation, and documentary studies. The results showed that the average understanding of the concept of gender still overlapped with the concept of sex. The characteristics of the dominant gender ideology were naturally patterned. This was influenced by social, cultural, and religious contexts and the general social perspective towards women. Although the discourse of gender equality had emerged in many ways, people in general still strongly believed in the differences between male and female. This is then strongly implied in the implementation of physical education teaching practices. Forms of domination in learning, differences in standards, as well as distinctions in patterns of communication and sanctions, are still phenomenal.